(x+10)(x-3)=25

Simple and best practice solution for (x+10)(x-3)=25 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (x+10)(x-3)=25 equation:


Simplifying
(x + 10)(x + -3) = 25

Reorder the terms:
(10 + x)(x + -3) = 25

Reorder the terms:
(10 + x)(-3 + x) = 25

Multiply (10 + x) * (-3 + x)
(10(-3 + x) + x(-3 + x)) = 25
((-3 * 10 + x * 10) + x(-3 + x)) = 25
((-30 + 10x) + x(-3 + x)) = 25
(-30 + 10x + (-3 * x + x * x)) = 25
(-30 + 10x + (-3x + x2)) = 25

Combine like terms: 10x + -3x = 7x
(-30 + 7x + x2) = 25

Solving
-30 + 7x + x2 = 25

Solving for variable 'x'.

Reorder the terms:
-30 + -25 + 7x + x2 = 25 + -25

Combine like terms: -30 + -25 = -55
-55 + 7x + x2 = 25 + -25

Combine like terms: 25 + -25 = 0
-55 + 7x + x2 = 0

Begin completing the square.

Move the constant term to the right:

Add '55' to each side of the equation.
-55 + 7x + 55 + x2 = 0 + 55

Reorder the terms:
-55 + 55 + 7x + x2 = 0 + 55

Combine like terms: -55 + 55 = 0
0 + 7x + x2 = 0 + 55
7x + x2 = 0 + 55

Combine like terms: 0 + 55 = 55
7x + x2 = 55

The x term is 7x.  Take half its coefficient (3.5).
Square it (12.25) and add it to both sides.

Add '12.25' to each side of the equation.
7x + 12.25 + x2 = 55 + 12.25

Reorder the terms:
12.25 + 7x + x2 = 55 + 12.25

Combine like terms: 55 + 12.25 = 67.25
12.25 + 7x + x2 = 67.25

Factor a perfect square on the left side:
(x + 3.5)(x + 3.5) = 67.25

Calculate the square root of the right side: 8.200609733

Break this problem into two subproblems by setting 
(x + 3.5) equal to 8.200609733 and -8.200609733.

Subproblem 1

x + 3.5 = 8.200609733 Simplifying x + 3.5 = 8.200609733 Reorder the terms: 3.5 + x = 8.200609733 Solving 3.5 + x = 8.200609733 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3.5' to each side of the equation. 3.5 + -3.5 + x = 8.200609733 + -3.5 Combine like terms: 3.5 + -3.5 = 0.0 0.0 + x = 8.200609733 + -3.5 x = 8.200609733 + -3.5 Combine like terms: 8.200609733 + -3.5 = 4.700609733 x = 4.700609733 Simplifying x = 4.700609733

Subproblem 2

x + 3.5 = -8.200609733 Simplifying x + 3.5 = -8.200609733 Reorder the terms: 3.5 + x = -8.200609733 Solving 3.5 + x = -8.200609733 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3.5' to each side of the equation. 3.5 + -3.5 + x = -8.200609733 + -3.5 Combine like terms: 3.5 + -3.5 = 0.0 0.0 + x = -8.200609733 + -3.5 x = -8.200609733 + -3.5 Combine like terms: -8.200609733 + -3.5 = -11.700609733 x = -11.700609733 Simplifying x = -11.700609733

Solution

The solution to the problem is based on the solutions from the subproblems. x = {4.700609733, -11.700609733}

See similar equations:

| h^2-5h-30=0 | | y-40+3=-40 | | 100-a=10% | | 9x-9=x | | (7-8)x=-29 | | -16=2v+8 | | x^4-y+xy-x^3=0 | | 10-a=10% | | Log(x-6)=2.75 | | 2x+5th=75 | | (1+u)(5u-8)=0 | | 8w=218 | | 11y+y= | | 15x-3(x+4)=6 | | 2(4x-6)=48 | | 4x^2-10=15 | | 32-t^5=0 | | 8a+4x=47fora | | 12(-4+6x)=13x+23(x+9) | | 2x+16=7x | | 6t-5=-29 | | 40=5(2Y+10) | | 8b-7b= | | y-3=9(x-0) | | 3y-5x=12+5y | | 12c-10c= | | 5y-50=8y-5+6y | | 4q+10=2q | | 7k+15=-13 | | 6x-4=3x-x-22 | | 0.6y=1.8 | | 1.5(x+12)-2x=-1 |

Equations solver categories